Confidence and Success of Counseling Practices for Islamic Guidance and Counseling Students - Zatrahadi, Muhammad Fahli; Nurjanah, Anisa Siti; Darmawati, Darmawati; Miftahuddin, Miftahuddin; Suhaimi, Suhaimi; Rahmad, Rahmad; Saputra, Aldi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2021)
One of the keys to successful counseling is the personal quality of the counselor. However, early counselors tend not to have these competencies. This study aims to determine the relationship between self-confidence and the successful implementation of student counseling. The research uses a quantitative approach with the correlational method. The sample in this study were 87 students who had studied counseling theory and practice and had practiced counseling. Data were analyzed using Pearson Product Moment with the help of SPSS 25 for Windows. The results show no relationship between the variables x and y, so it can be concluded that there is no significant relationship between self-confidence and the success of counseling.